TI_GERICHTE 14.2010.17 vom 26. April 2010 , Rigetto provvisorio. Contratto di locazione. Eccezione di compensazione - TI Tribunale d'appello (2010)
Rigetto provvisorio. Contratto di locazione. Eccezione di compensazione